Robber flies of South KoreaóII. South Korean species of the Subfamily Asilinae Latreille, 1802 (Diptera, Asilidae) - Young, Charles L. (Zootaxa, 2006)
Eight genera and 13 species within the subfamily Asilinae are recorded from South Korea. New records for the area include: Aneomochtherus sinensis (Ricardo, 1919), Asilella londti Lehr, 1989, Machimus aurulentus Becker, 1925, Machimus cf. pastshenkoae (Lehr, 1976), Mercuriana ussuriensis (Lehr, 1981), Neoitamus castaneipennis Tagawa, 1981, and N. zouhari Hradskv, 1960. Drawings of diagnostic features, a checklist, keys, and descriptions are included. All mentioned species are re-described based on specimens collected for this study.